Determinan Yang Mempengaruhi Jumlah Permintaan Kredit Pemilikan Rumah di Indonesia - Rifki Khoirudin Khoirudin (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2017)
Bank lending to the consumption sector has increased dramatically since Indonesia was hit by the economic crisis ten years ago. This happens because many large companies go bankrupt so that the corporate sector absorbs very little credit from banks. Banks are increasingly recognizing that opportunities in the consumer market are growing, where the risks they face are relatively smaller compared to those in the investment market. Assuming that the house is a basic necessity that does not have substitutes, the possibility for a consumer who wants to own a home either in cash or credit is simply adjusting the type of home that suits the ability with different income levels by each individual. In this research, the method used is multiple linear regression. From independent variable that is economic growth, loan interest rate and residential property price index able to influence dependent variable that is mortgage credit equal to 97,9%